2021
DOI: 10.1007/s11239-021-02617-x
|View full text |Cite
|
Sign up to set email alerts
|

Complement system component dysregulation is a distinctive feature of COVID-19 disease: a prospective and comparative analysis of patients admitted to the emergency department for suspected COVID-19 disease

Abstract: The complement system (CS) plays a pivotal role in Coronavirus disease 2019 (COVID-19) pathophysiology. The objective of this study was to provide a comparative, prospective data analysis of CS components in an all-comers cohort and COVID-19 patients. Patients with suspected COVID-19 infection admitted to the Emergency department were grouped for definite diagnosis of COVID-19 and no COVID-19 accordingly. Clinical presentation, routine laboratory and von Willebrand factor (vWF) antigen as well as CS components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
3
3
0
Order By: Relevance
“…Previously, we determined C5a levels in longitudinally collected serum samples from 49 patients suffering from C-19 with different clinical intensities and concluded that serum C5a levels remain high in severe cases of COVID-19 and are associated with the persistence of respiratory symptoms after hospital discharge ( 4 ). An increase in C5a proportional to the severity of the disease has been also reported in other studies using either plasma ( 1 , 2 , 6 ) or serum ( 3 5 ). The observation that C5a, normally cleared rapidly from the circulation ( 7 , 8 ), remains elevated in follow-up samples from COVID-19 convalescents made us investigate the source of this anaphylatoxin after the clearance of infection.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Previously, we determined C5a levels in longitudinally collected serum samples from 49 patients suffering from C-19 with different clinical intensities and concluded that serum C5a levels remain high in severe cases of COVID-19 and are associated with the persistence of respiratory symptoms after hospital discharge ( 4 ). An increase in C5a proportional to the severity of the disease has been also reported in other studies using either plasma ( 1 , 2 , 6 ) or serum ( 3 5 ). The observation that C5a, normally cleared rapidly from the circulation ( 7 , 8 ), remains elevated in follow-up samples from COVID-19 convalescents made us investigate the source of this anaphylatoxin after the clearance of infection.…”
Section: Discussionsupporting
confidence: 81%
“…4). An increase in C5a proportional to the severity of the disease has been also reported in other studies using either plasma (1,2,6) or serum (3)(4)(5). The observation that C5a, normally cleared rapidly from the circulation (7,8), remains elevated in follow-up samples from COVID-19 convalescents made us investigate the source of this anaphylatoxin after the clearance of infection.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Our results further showed that the complement components C4b-binding protein and its alpha chain [P04003], as well as C9 [P02748] were elevated in the post-COVID-19 patient group compared to the uninfected. Consistent evidence was provided by a study reporting C4 elevation in patients with possible SARS-CoV-2 infection held in the Emergency Department [ 17 ]. Similarly, another study on patients with severe COVID-19 found elevated deposits of C5a to C9 in biopsies of skin and lung tissue [ 18 ].…”
Section: Discussionsupporting
confidence: 73%